UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK AKHLAK SISWA KELAS VIII DI SMP BAHRUL BAGHFIROH MALANG - Abdul Khalik Serang; Ika Ratih Sulistiani; Ika Anggraheni (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Morals is a word used to term human assistance which is then resolved with good or bad conduct. In Islam, which is used to accept good or bad from a place someone is not in another place in Islam it self. Researchers used qualitative with the type of case study research. Data collection techniques using interviews, observation, and documentation. PAI Teacher's efforts are to shape students with the aim that students have good and noble character. supporting factors in the formation of learning of moral students are firstly in the cooperation of teachers in paying attention to students in school, the first is parents who teach Islamic teachings to children, the school environment that supports religious programs and finally learning methods. The inhibiting factors that are experienced are like students who are difficult to be disciplined, such as when the prayer starts. The teacher still has to read one student at a time to make sure there are students in the class or not. Then the picket teacher still has to instruct or guide students by ensuring that students can go to the mosque.